An improved high-throughput screening assay for tunicamycin sensitivity in Arabidopsis seedlings - McCormack, Maggie E.; Liu, Xiaoyu; Jordan, Melissa R.; Pajerowska-Mukhtar, Karolina M. (Frontiers in Plant Science, 2015)
Tunicamycin sensitivity assays are a useful method for studies of endoplasmic reticulum stress and the unfolded protein response in eukaryotic cells. While tunicamycin sensitivity and tunicamycin recovery assays have been previously described, these existing methods are time-consuming, labor intensive and subjected to mechanical wounding. This study shows an improved method of testing tunicamycin sensitivity in Arabidopsis using liquid Murashige and Skoog medium versus the traditional solid agar plates. Liquid medium bypasses the physical manipulation of seedlings, thereby eliminating the risk of potential mechanical damage and additional unwanted stress to seedlings. Seedlings were subjected to comparative treatments with various concentrations of tunicamycin on both solid and liquid media and allowed to recover. Determination of fresh weight, chlorophyll contents analysis and qRT-PCR results confirm the efficacy of using liquid medium to perform quantitative tunicamycin stress assays.